Prospective Science-Teachers’ Services Satisfaction: an Exploratory Studies in Private Education Institutions in Indonesia - Saiful Prayogi; Taufik Samsuri; Ni Nyoman Sri Putu Verawati; Rahmawati Rahmawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This study aims to explore the prospective science-teachers’ services satisfaction in private educational institution in Indonesia. Intended educational institution in this study is the Institute of Teacher Training and Education (IKIP) Mataram, Province of West Nusa Tenggara, Indonesia. This study is a survey research, where data is collected using a questionnaire containing the statement items of services satisfaction on the aspects of reliability, responsiveness, assurance, empathy, and tangibility. Questionnaires were given to prospective-teachers who were actively studying and felt the services provided by the institution. Respondents involved as many as 282 prospective science-teachers, each of respondents from three study programs namely biology education, physics education, and chemistry education. The results of measurements of prospective science-teachers’ services satisfaction in IKIP Mataram on the aspects of reliability, responsiveness, assurance, empathy, and tangibility in a row with very good responses of 17.59%, good responses of 60.64%, sufficient responses of 13.76%, and less responses of 8.01%. The recommendation in this study is that private education institutions need to continue to improve services in all aspects, especially the most dominant is the tangible aspect.